1992
DOI: 10.1103/physrevlett.69.3762
|View full text |Cite
|
Sign up to set email alerts
|

Solid-on-solid rules and models for nonequilibrium growth in 2+1 dimensions

Abstract: On the basis of a detailed stochastic simulation we find that nonequilibrium growth in 2+1 dimensions, within the simple solid-on-solid approximation, is surprisingly rich with its dynamical universality depending sensitively on the local atomistic relaxation rules of the growth model. We establish connections between our computed dynamical growth exponents for various physically plausible local growth models with those given by a recently proposed fourth-order nonlinear continuum diflferential equation.PACS n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
44
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(50 citation statements)
references
References 13 publications
5
44
1
Order By: Relevance
“…Our model is distinguished from that of BAS in that the four neighboring spins are of equidistance, while they are not in the BAS model. Interestingly, this difference of the local dynamic rules leads to different universality classes, which is in accordance with a recent claim that dynamic universality class depends on local dynamic rules in (2+1) dimensions [6]. We studied the model for both unbiased and biased cases, and found that our model belongs to the Edwards-Wilkinson (EW) [7] universality for the unbiased case and the AKPZ universality in the wea/c-coupling limit [4] for the biased case.…”
supporting
confidence: 91%
“…Our model is distinguished from that of BAS in that the four neighboring spins are of equidistance, while they are not in the BAS model. Interestingly, this difference of the local dynamic rules leads to different universality classes, which is in accordance with a recent claim that dynamic universality class depends on local dynamic rules in (2+1) dimensions [6]. We studied the model for both unbiased and biased cases, and found that our model belongs to the Edwards-Wilkinson (EW) [7] universality for the unbiased case and the AKPZ universality in the wea/c-coupling limit [4] for the biased case.…”
supporting
confidence: 91%
“…10,11 We will briefly survey some results obtained for models with modified rules and in higher dimensions in Sec. III.…”
Section: B Discrete Models Of Mbe Growthmentioning
confidence: 99%
“…Apart from the intrinsic theoretical interest, the motivation was a hope to better understand growth processes in molecular beam epitaxy ͑MBE͒ and other epitaxial growth techniques. Different variants of simplified ͑''toy''͒ discrete models with relaxation only after deposition, [5][6][7][8][9][10][11][12][13][14][15] as well as more realistic full diffusion ͑FD͒ models, 7, 16 -18 have been employed, and the question of whether they belong to a new universality class has been addressed. Early numerical calculations seemed to suggest that this is actually the case 6 -8,10,16 but more recent results 12,14,18,19 show that in many growth models with surface diffusion the true asymptotic behavior is either of the well-known Edwards-Wilkinson type ͑which is only logarithmically rough in dϭ3) or that growth is unstable.…”
Section: Introductionmentioning
confidence: 99%
“…Patterns growth in the Cahn-Hilliard Equation (used to model spinodal decomposition) are shown to exhibit three distinct stages. Two models of surface growth, namely the continuous Kardar-Parisi-Zhang (KPZ) model and the discrete Restricted-Solid-On-Solid (RSOS) model are shown to have different saturation exponents.PACS numbers: 47.54.+r,47.20.Hw,05.70.Np,64.75.+g,89.75.Kd,05.50.+q, In recent years, there has been a considerable amount of effort to analyze non-equilibrium interfacial growth and pattern formation in experimental and model systems [1,2,3,4,5,6,7,8,9,10]. The phenomena studied include spinodal decomposition [1,5,11,12], chemical pattern formation [4], surface growth [2,3,7,8] and epitaxial growth [9,10].…”
mentioning
confidence: 99%
“…The phenomena studied include spinodal decomposition [1,5,11,12], chemical pattern formation [4], surface growth [2,3,7,8] and epitaxial growth [9,10]. Microscopic modeling of these phenomena is highly complex, and most microscopic details of such structures depend on initial conditions and stochastic effects.…”
mentioning
confidence: 99%